2021
DOI: 10.3389/fmed.2021.637652
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Fibrosis Using Blood Markers and Logistic Regression in Southeast Asian Patients With Non-alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is one of the main causes of fibrosis. Liver biopsy remains the gold standard for the confirmation of fibrosis in NAFLD patients. Effective and non-invasive diagnosis of advanced fibrosis is essential to disease surveillance and treatment decisions. Herein we used routine medical test markers and logistic regression to differentiate early and advanced fibrosis in NAFLD patients from China, Malaysia, and India (n1 = 540, n2 = 147, and n3 = 97) who were confirmed by live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…For detailed information on diagnosis and enrolment criteria, please refer to our original publication. 18 Study 2-liver fibrosis study. A total of 709 participants including 382 HBV-related fibrosis patients (324 [stage 0-3] and 58 cirrhosis [stage 4]) and 327 healthy controls were recruited from the Shuguang Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, China.…”
Section: Discovery Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…For detailed information on diagnosis and enrolment criteria, please refer to our original publication. 18 Study 2-liver fibrosis study. A total of 709 participants including 382 HBV-related fibrosis patients (324 [stage 0-3] and 58 cirrhosis [stage 4]) and 327 healthy controls were recruited from the Shuguang Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, China.…”
Section: Discovery Setsmentioning
confidence: 99%
“…14 A group of conjugated 12α-hydroxylated (12α-OH) BAs significantly increased in NASH patients and liver fibrosis mouse models and were potential promoters of liver fibrosis. 15 Based on these, we constructed and validated several machine learning models to classify early (stage 0-2) and advanced (stage 3-4) hepatic fibrosis using BAs and clinical parameters in patients with hepatitis B and C virus infections 16,17 and NAFLD 18 patients. Furthermore, we discussed the mechanistic links between BAs and HCC and highlighted the strategies and cutting-edge technologies to target gut microbiota-dependent alterations in BA metabolism in the context of cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, hepatitis virus can inhibit bone marrow megakaryocytes, which impairs platelet production, thereby reducing platelet count and their ability to aggregate, and increasing mean platelet volume and width. 42,43 Liver damage is associated with increases in the serum activities of AST and ALT, and these are commonly used as markers of hepatocyte injury. 44,45 These parameters are also used as a means of diagnosing NAFLD early, and the identification of a high-normal serum ALT activity is of great significance for the early prevention of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that fibrosis could be diagnosed using blood barkers and Logistic regression in Southeast Asian patients with NAFLD. 9 However, there were no related studies describing biomarkers, which can predict the development of NAFLD in T2DM patients, which could cause the high risk of occurrence of CVD or severe liver diseases. Therefore, it is urgent and important to find simple, noninvasive diagnostic biomarkers that can help in the early detection and understanding of the mechanism involved in the formation of NAFLD in T2DM patients to prevent the occurrence of CVD and HCC.…”
Section: Introductionmentioning
confidence: 99%